Cross Country Event Management System for Malaysian Secondary School - Khew, Li Tien (2021)
Cross country event can be an enriching experience for most Malaysian secondary school students. However, the management for such event can be exhaustive due to the sizeable load of recording and sorting large groups of runners while maintaining focus under the hot weather of Malaysia. In addition to most Malaysian secondary school employing manual logging method for recording runners, the result of recording can be less imprecise and slow. The solution to an exact recording and automation of task for event personnel is by employing dedicated tracking equipment such as chips and tracking mat, but will remain as a poor choice for financial management. This project intends to ease the event management process and reduce the downsides of current common recording methods through the usage of QR code scanning for recording participants, and through providing tools for finalizing ranking based on the recorded data. Rapid Application Development methodology was adopted and functionalities prototyping was thoroughly emphasized and performed during the system development. The system was developed with the guidance of the requirements elicited through the evaluation from the survey completed by SMJK Katholic PJ and exploratory study on available resources. User Acceptance Test and System Usability Test was performed with several participants of secondary schools and most had identified that the system is able to perform the core tasks with ease of learning. Additionally, evaluation done such as items encompassing unit testing, integration testing, system testing and static code reviewed had positively indicated that the system is stable. In conclusion, the project is believed to have achieved all the elicited objectives of developing a cross country event management system that overcomes the weakness of manual logging method by employing QR scanning for recording and providing tools for finalizing results.